2009
DOI: 10.1007/s00572-009-0259-9
|View full text |Cite
|
Sign up to set email alerts
|

Extraradical development and contribution to plant performance of an arbuscular mycorrhizal symbiosis exposed to complete or partial rootzone drying

Abstract: Sweet potato plants were grown with or without Glomus intraradices in split-root pots with adjacent root compartments containing a soil with a low availability of phosphate. One fungal tube, from which root growth was excluded, was inserted into each root compartment. During 4 weeks before harvest, the soil moisture level in either both or only one of the two root-compartments of each pot was decreased. Controls remained well watered. Low soil moisture generally had a negative effect on the amount of extraradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 40 publications
3
26
0
1
Order By: Relevance
“…Particularly when the soil nutrient availability is low, AM fungal contribution to plant nutrient uptake and growth can be significant (Neumann and George, 2004;Neumann et al, 2009). In return, the host plant supplies the AM fungus with photoassimilates in the form of hexose.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly when the soil nutrient availability is low, AM fungal contribution to plant nutrient uptake and growth can be significant (Neumann and George, 2004;Neumann et al, 2009). In return, the host plant supplies the AM fungus with photoassimilates in the form of hexose.…”
Section: Introductionmentioning
confidence: 99%
“…As mycorrhizal colonization precedes the sporulation of AMF, the reduction in water availability can affect first this step, and works such as that of Neumann et al (2009) demonstrated that plants of Ipomoea batatas L. subjected to water stress for seven days had reduction in root colonization produced by G. intraradices Schenck & Smith. Conversely, Schellenbaum et al (1998) found no reduction in mycorrhizal colonization by an isolate of G. mosseae (T. H. Nicolson Gerd.)…”
Section: Water Availability and Sporulation Of Amfmentioning
confidence: 97%
“…Under experimental conditions, a gradual reduction of soil moisture over four weeks resulted in increased production of external mycelium and sporulation of Glomus intraradices Schenck & Smith (Neumann et al, 2009). However, in extreme drought conditions a reduction of AMF sporulation occurs, but an increase in the formation of propagules can additionally occur depending on the form and duration of water stress, which is influenced also by the host and fungal species (Augé, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…The water loss from the split-root systems with nonuniform water treatments was estimated based on the water replacement needs of the containers with uniform water treatments. Considering lower estimated SWC in the W compartments whose counterpart compartments were subjected to D instead of W (Neumann et al 2009), c. 10 % of daily water depletion from those W compartments was supplemented additionally. Estimation of daily water needs for each compartment is shown in Supplementary Table 1.…”
Section: Biological Materials and Growth Conditionsmentioning
confidence: 99%